Morphological analysis of Laser Surface Texturing effect on AISI 430 stainless steel - Moldovan, Edit Roxana; Concheso Doria, Carlos; Ocaña, Jose Luis; Istrate, Bogdan; Cimpoesu, Nicanor; Baltes, Liana Sanda; Stanciu, Elena Manuela; Croitoru, Catalin; Pascu, Alexandru; Munteanu, Corneliu; Tierean, Mircea Horia (MDPI Materials, 2022)
Laser surface texturing (LST) is a method to obtain micro-structures on the material’s surface for improving tribological performances, wetting tuning, surface treatment, and increasing adhesion. The material selected for LST is AISI 430 ferritic stainless steel, distinguished by the low cost in manufacturing, corrosion resistance, and high strength at elevated temperature. The present study addresses the morphology of new pattern designs (crater array, ellipse, and octagonal shapes). The patterns are applied on the stainless-steel surface by a non-contact method with high quality and precision nanosecond pulsed laser equipment. The investigation of laser parameter influence on thermal affected area and micro-structures is accomplished by morphological and elemental analysis (SEM + EDX). The parameters of the laser micro-patterning have a marked influence on the morphology, creating groove-type sections with different depths and recast material features. From the SEM characterization, the highest level of recast material is observed for concentric octagon LST design. Its application is more recommended for the preparation of the metal surface before hybrid welding. Additionally, the lack of the oxygen element in the case of this design suggests the possible use of the pattern in hybrid joining.